PROPOSED RULE 101-20. 109-10 REGULATIONS OF SMOKING - KORNEGAY,HR (Tufts Archival Research Center, 2007)
Missing Attachments; Tobacco Institute memo discussing General Services Administration's (GSA) smoking regulations. Accuses new regulations of being unwise, unnecessary, and beyond the scope of GSA authority. Argues that there is no valid scientific evidence showing negative effects of secondhand smoke.